Gambaran profil lipid pada remaja obes di Kota Bitung - Senduk, Billy; Bodhi, Widdhi; Kepel, Billy J. (Universitas Sam Ratulangi, 2016)
Abstract: Obesity is a condition of increased body weight because of sexcessive fat accumulation in the body. The prevalence of obesity is increasing becoming one of the things that concern in Indonesia, especially in urban areas. Obesity is also associated with blood lipid levels that can cause dyslipidemia. Lipid profile can be observed by levels of total cholesterol, LDL, HDL, and triglycerides. Dyslipidemia has related with the occurrence of atherosclerosis and lead to acute myocardial infarction. This research used a descriptive observational study with cross sectional design. The samples were taken from adolescents obesity as measured by waist circumference. The amount of sample that is willing to sign an informed consent 50 samples. Based on the measurement of waist circumference of 966 students obtained 220 obese students (22.8%) and were taken 50 obese students who are willing to become a sample. From the results of blood samples examination of the 50 obese students was obtained 13 students (26%) had total cholesterol levels above normal, 31 students (62%) had HDL levels below normal, 41 students (82%) had LDL levels above normal, and 6 students (12%) have triglyceride levels above the normal value.Keywords: obesity, adolescents, lipid profileAbstrak: Obesitas adalah kondisi meningkatnya berat badan akibat akumulasi lemak berlebihan dalam tubuh. Prevalensi obesitas yang terus meningkat menjadi salah satu hal yang dikhawatirkan di Indonesia, terutama di perkotaan. Obesitas juga berkaitan dengan kadar lipid darah yang dapat menyebabkan dislipidemia. Profil lipid adalah keadaan lemak yang dilihat dari kadar kolesterol total, LDL, HDL, dan Trigliserida. Dislipidemia memiliki hubungan erat dengan terjadinya aterosklerosis dan berujung pada infark miokard akut. Penelitian ini dilakukan dengan menggunakan metode observasional deskriptif dengan desain cross sectional study. Sampel penelitian diambil dari remaja obesitas yang diukur berdasarkan lingkar pinggang. Jumlah sampel penelitian yang bersedia menandatangani informed consent 50 sampel. Berdasarkan hasil pengukuran lingkar pinggang 966 siswa didapatkan 220 siswa (22,8%) mengalami dan diambil 50 siswa obesitas yang bersedia untuk dijadikan sampel penelitian. Dari hasil pemeriksaan sampel darah terhadap 50 siswa obesitas tersebut didapatkan 13 siswa (26%) memiliki kadar kolesterol total diatas normal, 31 siswa (62%) memiliki kadar HDL dibawah normal, 41 siswa (82%) memiliki kadar LDL diatas normal, dan 6 siswa (12%) memiliki kadar trigliserida diatas nilai normal.Kata kunci: obesitas, remaja, profil lipid